A brief view of factors that affect plant virus evolution - Butković, Anamarija; González, Rubén (Frontiers in Virology, 2022)
Viruses are highly evolvable biological entities. In general, better understanding of virus evolution will lead to better management of current diseases and prevention of future ones but it will also contribute to a better understanding of evolutionary processes and their dynamics, which can be translated to other pathosystems as well. Many factors shape the evolution of viruses. In this review we give a general overview of most relevant described factors that determine the evolution of plant viruses and describe the evolutionary particularities of these kind of viruses. Besides its importance in a better management of agricultural diseases, the study of plant virus evolution can give important insights into the general mechanisms and factors that shape virus evolution.